Mental disorders in older adults : fundamentals of assessment and treatment - Zarit, Steven H. (Guilford Press, 1998)
In this book, the authors begin by describing the normal processes of growing older, showing how healthy individuals learn adaptive coping skills to compensate for mild cognitive decline. The book then details the assessment and treatment of the disorders most commonly experienced by older adults, including Alzheimer's disease, depression, anxiety, delirium, and paranoia. The authors delineate psychological evaluation methods with particular relevance to for elderly clients, including techniques to assess mental competence and to differentiate dementia from other disorders. For each common disorder, a variety of therapeutic approaches are examined--including behavioral, cognitive-behavioral, and interpersonal psychotherapies. As the authors demonstrate, even degenerative conditions often contain treatable components. The volume also provides important information on frequently prescribed medications, facilitating more effective collaboration between mental health and medical professionals. This book is intended for all mental health clinicians who work with older adults and serves as a text for courses in psychology and aging, gerontology, and geriatric psychiatry.